ANALISIS KEBUTUHAN SISTEM INFORMASI BISNIS TERINTEGRASI PADA KOPERASI SD NEGERI 064983 DI ERA DIGITAL - Dwi Fany Fransiska Dewi Butar Butar (JURNAL WIDYA, 2025)
The development of information technology in the digital era requires organizations, including school cooperatives, to adapt through the utilization of integrated information systems. The Cooperative of SD Negeri 064983 still relies on manual recording and non- integrated simple applications, resulting in data management inefficiencies and reporting difficulties. This study aims to analyze the needs of an integrated business information system in the cooperative. The research method uses a qualitative descriptive approach with data collection techniques including observation, interviews, and documentation. The results indicate the need for an integrated system covering membership, inventory, sales transactions, financial management, and automated reporting modules. The implementation of an integrated business information system is expected to improve work efficiency, data accuracy, financial transparency, and service quality. Keywords: business information system, integrated system, cooperative, system needs, digital era